პტოლემაიოსის „ალმაგესტისა“ და „ტეტრაბიბლოსის“ ურთიერთსაპირისპირო შეფასებებისათვის - ფოფხაძე გვანცა (ლოგოსი, 2023)
Claudius Ptolemy is rightly considered one of the eminent astronomers of antiquity. His earliest and the chief work in astronomy “Almagest”, also known as “Mathematical syntaxis”, dominated astronomical science until it was overshadowed by greater achievements of Copernicus. His another work “Tetrabiblos” – enjoyed the same authority among astrologers, as holy bible among Christians. The latter is some kind of complement to the former. “Almagest” shows how it is possible to derive geometrical models from a set of observations to predict positions of celestial bodies at any given time. “Tetrabiblos” tries to prove, how above stated positions influence on terrestrial things. One thing they have in common is Ptolemy’s love for systematization. In this article: “For the controversial assessment of Ptolemy’s “Almagest” and “Tetrabiblos” we will discuss how Ptolemy’s urge for theorization and systematization was perceived and appreciated by the next generations of scientists.